1995
DOI: 10.1116/1.587909
|View full text |Cite
|
Sign up to set email alerts
|

Domain structure and polarization reversal in ferroelectrics studied by atomic force microscopy

Abstract: Hatano, J.; Takahashi, K.; and Tokumoto, H., "Domain structure and polarization reversal in ferroelectrics studied by atomic force microscopy" (2005 The ferroelectric domain structure and its dynamics under applied electric field have been studied with nanoscale resolution by atomic force microscopy ͑AFM͒. Two mechanisms responsible for the contrast between opposite domains are proposed: large built-in domains are delineated in friction mode due to the tip-sample electrostatic interaction, and small domains cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Herringbone domains appear only above a certain critical diameter, above which the domain size dependence gets modified: The stripes scale as the square root of the herringbone width, while the herringbone width scales as r 2=3 (where r is the grain radius), so that the stripe width ends up scaling as r 1=3 (Arlt, 1990). Randall and co-workers also studied in close detail the domain size dependence within ceramic grains (Cao and Randall, 1996;Randall et al, 1998) and concluded that the square root dependence is valid only within a certain range of grain sizes, with the scaling exponent being smaller than 1 2 for grains larger than 10 m, and bigger than 1 2 for grains smaller than 1 m. The same authors observed cooperative switching of domains across grain boundaries, as did Gruverman et al (1995aGruverman et al ( , 1995bGruverman et al ( , 1996, evidence that the elastic fields associated with ferroelastic twinning are not easily screened and can therefore couple across boundaries.…”
Section: Domains In Nonplanar Structuresmentioning
confidence: 77%
“…Herringbone domains appear only above a certain critical diameter, above which the domain size dependence gets modified: The stripes scale as the square root of the herringbone width, while the herringbone width scales as r 2=3 (where r is the grain radius), so that the stripe width ends up scaling as r 1=3 (Arlt, 1990). Randall and co-workers also studied in close detail the domain size dependence within ceramic grains (Cao and Randall, 1996;Randall et al, 1998) and concluded that the square root dependence is valid only within a certain range of grain sizes, with the scaling exponent being smaller than 1 2 for grains larger than 10 m, and bigger than 1 2 for grains smaller than 1 m. The same authors observed cooperative switching of domains across grain boundaries, as did Gruverman et al (1995aGruverman et al ( , 1995bGruverman et al ( , 1996, evidence that the elastic fields associated with ferroelastic twinning are not easily screened and can therefore couple across boundaries.…”
Section: Domains In Nonplanar Structuresmentioning
confidence: 77%
“…The piezoelectric property of the g-C 3 N 4 nanosheets is examined using PFM. For piezoelectric materials, an applied voltage will cause a measurable deflection of the cantilever 18 . The thickness of the fabricated nanosheets is in the order of only a couple nanometers, while the length and width can range from 500 nm to a few mm.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] However, it has often been a matter of debate to what extent the magnitude of PFM signals can be reproduced and quantified experimentally. Some researchers express doubts whether the magnitude of PFM signals of two different experiments can be reasonably reproduced and refer to PFM measurements taken on periodically poled lithium niobate (PPLN) on different days which are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%